Solvent Base Lamination Process Substitution to Solvent Freefor Production Cost Savings - Saarah Putri; Handika Dany Rahmayanti; Yessy Yerta Situngkir (P3M Politeknik Negeri Media Kreatif, 2025)
The packaging industry in Indonesia is growing rapidly, especially in production cost efficiency. One of the important stages is the lamination process, which is the incorporation of the printing film and sealing film using adhesive. Solvent-free lamination technology emerged as an environmentally friendly alternative because it does not use solvents. This study uses a quantitative method to analyze the impact of technology change from solvent base to solvent free on cost efficiency. The results showed that laminates with 15 micron Nylon and 85 micron LLDPE C8 still produced bonding strength in accordance with industry standards. Solvent-free technology is more efficient because it does not require a drying chamber, so energy consumption is lower. Although there is still a small amount of solvent residue, it is still cleaner and more economical to use. Substitution to this technology shows great potential in reducing production costs without compromising product quality. Therefore, solvent free is an environmentally friendly and efficient solution for the flexible packaging industry in Indonesia.